Research note: Testing the tourism-led growth hypothesis for Singapore - an empirical investigation from bounds test to cointegration and Granger causality tests - Katircioglu, Salih (Sage Publications Ltd, 2010)
This paper empirically investigates the tourism-led growth (TLG) hypothesis in the case of Singapore by employing the bounds test for cointegration, error correction models and Granger causality tests using annual data from 1960 to 2007. The results confirm the existence of a long-term equilibrium relationship between international tourism and economic growth in the case of Singapore; real income growth converges significantly toward its long-term equilibrium level of 51.4% in the TLG model. The major finding of this study is that the TLG hypothesis is confirmed for the Singaporean economy in the long term as a result of conditional Granger causality tests.
Keywords: tourism-led growth; economic growth; bounds test; conditional causality; Singapore